The Death of Aztec Tenochtitlan, the Life of Mexico City - Mundy, Barbara E. (Book collections on Project MUSE., 2015)
"In 1325, the Aztecs founded their capital city Tenochtitlan, which grew to be one of the world's largest cities before it was violently destroyed in 1521 by conquistadors from Spain and their indigenous allies. Re-christened and reoccupied by the Spanish conquerors as Mexico City, it became the pivot of global trade linking Europe and Asia in the 17th century, and one of the modern world's most populous metropolitan areas. However, the Aztec city of Tenochtitlan and its people did not entirely disappear when the Spanish conquistadors destroyed it. By reorienting Mexico City-Tenochtitlan as a colonial capital and indigenous city, Mundy demonstrates its continuity across time. Using maps, manuscripts, and artworks, she draws out two themes: the struggle for power by indigenous city rulers and the management and manipulation of local ecology, especially water, that was necessary to maintain the city's sacred character. What emerges is the story of a city-within-a city that continues to this day"--